Induced systemic resistance by Beauveria bassiana in soybean plants and the effects on Spodoptera frugiperda - Marassatto, Carla Mariane (2022)
Beauveria bassiana is an entomopathogenic fungus as well as an endophyte. In Brazil, it is widely used by foliar applications as a biological control agent. The pest herbivory in plants colonized by this endophytic entomopathogenic fungi could result in secondary effects, and the knowledge about plant-induced defenses against pests resulting from the symbiont relationship of plant-fungi endophytic is limited. This study aimed to evaluate the secondary effects of endophytic colonization of B. bassiana (strain ESALQ PL63) triggered by herbivory of Spodoptera frugiperda. Soybean plants were inoculated in one trifoliate, and 2nd instar S. frugiperda were fed on non-inoculated leaves for eight days (first experiment) or until pupation (second experiment). The induced systemic resistance was evaluated by gene expression from main pathways (third experiment), salicylic acid (PR2), jasmone acid (MYC2 and PR3), and ethylene (ERF1). The treatments comprised non-inoculated plants and B. bassiana-inoculated plants, with or without herbivory of S. frugiperda. Plants were assessed 5, 15, and 30 days after inoculation. After eight days of herbivory, S. frugiperda larvae fed on B. bassiana-inoculated plants presented lower body mass and foliar area consumption. Endophytic colonization by B. bassiana also resulted in significant reductions in larval and pupal survival, lower larval span, and female fecundity, although the period until adult emergence was not affected. The pupal weight was not affected by herbivory in plants inoculated with B. bassiana; otherwise, some pupae were stiff, smaller, and malformed. At five days post-inoculation ERF1 gene was highly expressed in non-inoculated plants with herbivory compared to the slight response in B. bassiana-inoculated plants. The expression from ET-signaling represented by the ERF1 gene after 5 and 15 days post-inoculation had high response levels in the treatments of S. frugiperda herbivory (non-inoculated plants and inoculated plants), showing recognition of Herbivore-Associated Molecular Patterns (HAMPs) and Damage-Associated Molecular Patterns (DAMPs) after the herbivory. An increase of the MYC2 gene from the jasmonate acid pathway was observed after 15 days; a slight rise in PR3 was observed in B. bassiana-inoculated plants without herbivory, indicating a precursor production from jasmonate acid. The salicylic acid represented by the Pathogenic-related protein PR2 had lower regulation in all periods. The cross-talk between the acid salicylic and jasmonic acid signaling was demonstrated by lower and higher expression levels, respectively. At 30 days post-inoculation, the gene MYC2 in B. bassiana-inoculated plants decreased when compared with non-inoculated plants both with herbivory; thus, the induction of defense by plants inoculated with B. bassiana did not occur in this period. The presented study highlights the potential of B. bassiana as an endophytic to protect soybean plants against S. frugiperda.